Comparison of endovascular microwave ablation and traditional vein stripping for lower extremities varicose veins: a retrospective study - Cheng, Chunfa; Yang, Yifei; Zhu, Siqi (Vojnosanitetski pregled, 2025)
Background/Aim. Varicose veins typically occur in the superficial veins of the lower extremities and are a significant manifestation of chronic venous disease. Patients’ symptoms may vary depending on the pathogenesis, location, and severity of chronic venous disease. The aim of this study was to examine the efficacy of endovascular microwave ablation (EMA) and conventional high ligation with saphenous vein stripping in managing lower extremity varicose veins. Methods. This retrospective study included 100 patients diagnosed with unilateral varicose veins of the lower extremity. Of these, 50 underwent ultrasound-guided EMA (EMA group), and 50 received traditional vein stripping (traditional group). We assessed and compared operative duration, blood loss during surgery, number of incisions, hospital stay length, and postoperative complications across both groups. Additionally, the Venous Clinical Severity Score (VCSS) and Aberdeen Varicose Vein Questionnaire (AVVQ) were evaluated at 6 and 12 months postoperatively to determine treatment effectiveness. Results. All procedures were completed in the 100 cases. The EMA group had considerably reduced operating durations, less blood loss, fewer incisions, and abbreviated hospital stays relative to the traditional group (p < 0.05). Differences in subcutaneous bruising, hematoma formation, and skin burns across the groups were statistically significant (p  0.05). The preoperative and postoperative groups showed no substantial difference in VCSS and AVVQ scores (p > 0.05). However, both VCSS and AVVQ scores improved at 6 and 12 months post-surgery (p < 0.05). Conclusion. Clinical evaluation indicates that EMA’s effectiveness is comparable to traditional vein stripping in treating lower extremity varicose veins. EMA also presents safety advantages, suggesting its broader adoption in clinical settings.
Keywords: ablation techniques; ligation; lower extremity; saphenous vein; treatment outcome; varicose veins